Analisis Nilai Edukasi dalam Film UP Karya Walt Disney - Nuur Adila Kumala Dewi; Indri Kustantinah; Laily Nur Affini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This research aim to the values of character education in the movie UP. The purpose of this research is to identify the types of educational values contained in the movie UP and to find out the types of educational values that appear in the movie UP. This research was conducted using qualitative research method. Data sources were taken from the entire movie UP and the transcript of the movie UP downloaded from the internet. The movie UP focuses on the use of educational values and types of educational values. The results of this study, in the movie UP found several educational values that appear. The types of educational values contained in the movie UP which is divided into two types, value of being including; honesty, bravery, confidence, self-discipline, and purity. On the other hand, value of giving including, loyalty, respect, love and affection, not being selfish, being kind and friendly, and fair and humanist. From this study, the researcher hopes that after reading this research, readers understand about educational values and can apply in everyday life.